Apomorphine - pharmacological properties and clinical trials in Parkinson's disease. (December 2016) - Jenner, Peter; Katzenschlager, Regina
Abstract: Apomorphine is often considered an archetypal dopamine agonist used in the treatment of Parkinson's disease (PD). However, it can be clearly differentiated from most other commonly used dopamine agonists on the basis of its pharmacology and on its unique clinical profile. Like levodopa and dopamine, apomorphine acts as a potent, direct and broad spectrum dopamine agonist activating all dopamine receptor subtypes. It also has affinity for serotonin receptors, and α-adrenergic receptors. Apomorphine is usually titrated to a dose that provides an equivalent antiparkinsonian response to that provided by levodopa, and its subcutaneous delivery allows a rapid onset of action, usually within 7–10 min. The mode of apomorphine delivery impacts on its clinical profile so as to provide two very different approaches to therapy in PD. When administered as an acute subcutaneous injection, it induces reliable and rapid relief from OFF periods underscoring its utility as a rescue medication. When given as a subcutaneous infusion, it significantly improves overall daily OFF time and there is also evidence to suggest that, in those patients who replace most or all of their oral drugs with apomorphine infusion, dyskinesia may also improve. In this paper, we review the rich pharmacology of apomorphine and review its efficacy in PD based on data from clinical trials. Highlights: Apomorphine has a unique receptor pharmacology and clinical profile. Acute subcutaneous apomorphine injections provide rapid relief of OFF periods. Apomorphine infusions improve overall daily OFF time in patients with advanced PD.